Deficient intake of energy and macronutrients in female university students assessed by composite samples. - Khattak, Muhammad Muzaffar Ali Khan; Khan, M. N.; Khan, A. (Universiti Sains Malaysia, 2007)
Methodology : Twenty female students were registered from the female hostel of the NWFP, Agricultural University, Peshawar-Pakistan for the assessment of energy and macronutrients (protein, carbohydrate & fats) intakes by duplicate food samples. The age, weight and height of the students were recorded on the day of the registration. The students were asked to collect duplicate food samples for seven days i.e. breakfast, lunch & dinner and whatever else ate during the day. The daily food samples were bulked and composite samples were prepared for a week time. From the body weight & heights of the students the BMI was determined according to the formula; weight in kgs/ (height in meters) 2 as described by the (Bray, 1978). The skin-folds were assessed by using the adipometer and the percent body fats of the students were assessed from the body fat measurement chart for women provided in the manual of the adipometer (ACCU-MEASURE FINESS 2000).The collected duplicate food samples were blended with the help of common kitchen food blender on the next day of the last collection. The samples were analyzed for the macronutrients namely protein, carbohydrates and fats by the A.O.A.C method and consequently the energy was calculated. The energy values of the composites samples were determined by multiplying the daily eaten protein, carbohydrates and fats with 4, 4 and 9 respectively. The anthropometric and dietary intakes were compared with the international norms namely American Dietetic Association (ADA), World Health Organization (WHO) and Health Welfare Canada Nutrition Recommendation. The means were compared for the various parameters with the aforementioned norms as appropriate. The mean and standard deviation for the different aforementioned variables were determined by using a statistical package MINITAB (release 8.2) Inc. State. Drive. USA.